The Phenomenon of Elderly Street Vendors in the Jam Gadang Tourism Area Bukittinggi City - Gita Ramadhani; Selvi Kasman; Emzia Fajri (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This thesis is entitled "The Phenomenon of Elderly Street Vendors in the Clock Tower Tourist Area of Bukittinggi City". The aim of this research is to describe the views of the public and tourists towards elderly street vendors, the factors behind elderly street vendors continuing to choose to trade in the Jam Gadang tourist area of Bukittinggi City. The theory used in this thesis is the phenomenological theory of Edmund Husserl. The method used by the author is a qualitative method, with data collection techniques namely observation, interviews and documentation. The findings from this research are that the factors behind the elderly continuing to choose to trade in the Jam Gadang tourist area are economic factors, social factors and health factors. The views of the public and tourists towards these elderly street vendors do not have a problem with the existence of the traders and some tourists also feel respect for the existence of these elderly street vendors.